Administrative decentralization program and the emergence of a new local government system in Bangladesh - Ahmed, Ashrafuddin (1990)
Giving importance to the problems of underdevelopment, the successive governments in Bangladesh from its independence in 1972 prioritized the development of the rural population but short of developing a viable local government system. Hence, the quality of life of the people ofBangkideshfurther degenerated. Realizing this, President Ershad upon assuming office in 1982, introduced an administrative decentralization program with an objective of transforming their local government units into self-reliant ones. This decentralization measure was implemented through the democratization of the rural local government units with elected chairmen and the territorial reorganization of the administrative units of districts and sub-divisions. Significant administrative and political changes are now being observed in the local government system. However, to achieve a faster and more effective rural development, adequate time and continuity in direction must be insured.
Keywords: Decentralization -- Bangladesh; Local governance -- Bangladesh; Bangladesh -- Politics and government